Identification of breast cancer associated altered DNA methylation in peripheral blood using MALDI-TOF mass spectrometry - Yang, Rongxi; Burwinkel, Barbara (Annals of oncology, 2016)
© The Author 2016. Published by Oxford University Press on behalf of the European Society for Medical Oncology. All rights reserved. For permissions, please email: journals.permissionsoup.com.Background: Breast cancer (BC) is the leading cause of cancer-related mortality in women worldwide. Changes in DNA methylation in peripheral blood could be associated with malignancy at early stage. However, the BC-associated DNA methylation signatures in peripheral blood were largely unknown.Methods: Illumina 27K Methylation Array and Illumina 450K Methylation Array for the discovery of BC-related aberrant methylation sites in peripheral blood. The top hints were selected and validated using the MALDI-TOF Mass Spectrometry (MassARRAY, Agena Bioscience, Inc.) in two independent case-control studies with subjects from different centers. Gene expression levels were measured by real-time PCR and correlated with methylation. The clustering of samples by multiple CpG sites from a total of eight genes was realized by logistic regression. Receiver operating characteristic curve analyses...